Functional Expression of a DNA-Topoisomerase IB from Cryptosporidium parvum - César Ordóñez (Journal of Biomedicine and Biotechnology, 2009)
Cryptosporidium parvum, one of the most important causative organisms of human diarrheas during childhood, contains a monomeric DNA-topoisomerase IB (CpTopIB) in chromosome 7. Heterologous expression of CpTopIB gene in a budding yeast strain lacking this activity proves that the cryptosporidial enzyme is functional in vivo. The enzymatic activity is comprised in a single polypeptide, which contains all the structural features defining a fully active TopIB. Relaxation activity of the yeast extracts was detected only when CpTopIB ORF was expressed in a yeast expression system showing time and protein dependence under steady state kinetic conditions. The susceptibility of CpTopIB-transformed yeast to the irreversible inhibitor camptothecin and its water-soluble derivatives (topotecan and SN-38) was assessed.